THE INFLUENCE OF EASTERN PHILOSOPHY ON WESTERN LITERATURE - Qadamova Ruhshona Habibullayevna; Matjonova Qurvonbika O‘rinboyevna; Abdurakhmanova Diana Valerevna (TADQIQOTLAR.UZ, 2024)
Abstract: This thesis explores how Eastern philosophy has influenced Western literature, focusing on the key philosophical ideas from Hinduism, Buddhism, Taoism, and Confucianism that have been integrated into the works of notable Western authors. By analyzing the contributions of Transcendentalism, Modernism, Postmodernism, and contemporary literature, the paper shows how Eastern thought has helped reshape Western literary narratives. Key figures such as Ralph Waldo Emerson, T.S. Eliot, and Hermann Hesse are examined to highlight this cross-cultural exchange. The study concludes by showing the continued impact of Eastern philosophies on the global literary landscape.